Transforming inclusive practices in Islamic-based early childhood education: A case study in Indonesia - Malik, Dien Nurmarina; Prabowo , Swasto Imam Teguh (Journal of Early Childhood Care and Education, 2024)
Despite growing global attention to inclusive education, limited research has explored its implementation within Islamic-based early childhood contexts in Indonesia. This study investigates how inclusive education is understood and practiced by teachers in early childhood education (PAUD) ‘Aisyiyah, a long-standing Islamic early childhood provider. Using qualitative methods—observations and interviews during teacher training across five provinces—the study reveals a paradigmatic shift among educators from deficit-based to strengths-based views of diversity. Practically, teachers adopted differentiated instruction, multimodal strategies, and assistive technologies. Religious values rooted in compassion and social justice underpin these inclusive practices. However, challenges such as limited resources and inconsistent policy implementation remain. The study calls for stronger multi-stakeholder collaboration, policy reinforcement, and investment in teacher capacity development to support inclusive ECE aligned with Indonesia’s 2045 vision.